SERUM CORTISOL IN DAIRY CATTLE WITH OVARIAN CYST AND THE SUCCESSFUL TREATMENT OF CYST WITH GnRH PLUS POTASSIUM IODIDE - PUSHP, MK; PUROHIT, GN; KUMAR, S (The Indian Journal of Animal Reproduction, 2016)
Dairy cattle having ovarian cysts (n=40) were randomly treated with GnRH analogue (40 μg, i.m.), potassium iodide (KI, 10 g for 5 days, p.o.), GnRH analogue + KI or Ovsynch protocol. The maximum cyst disappearance and presence of a luteal mass 7 days post-treatment was observed following treatment with GnRH analogue + oral KI (80%) or GnRH analogue (70%), followed by ovsynch (50%), whereas KI therapy was ineffective. Plasma cortisol in dairy cattle with ovarian cysts was similar before and after treatment. In brief, plasma cortisol remained similar during pre- and post-treatment period in cattle displaying ovarian cyst and the ovarian cyst can be best treated with GnRH plus KI treatment.
Keywords: Cattle; Cortisol; GnRH; Ovarian cyst; Potassium iodide